Interpersonal values and their relation to attributional styles in fifth high school students - Tueros C., Rosa (2013)
This research aimed to establish the degree of relationship between interpersonal values and attributional styles of male and female students of the 5th year of secondary education. We used a descriptive correlational method, the sample consisted of 400 students, distributed in proportion to the population. The research was carried out, using the attributional style questionnaire and the Interpersonal Values Questionnaire SIV Leonard Gordon 1977. The results indicate according to the Spearman correlation coefficient exists correlation significant (p<0.05) between the different values interpersonal Support, Conformity, Recognition and Independence with attributional styles in the area of Academic  Achievement and Interpersonal Relations. Instead no significant correlations between Interpersonal Values Compassion and Leadership attributional styles in Areas of Academic Achievement and Interpersonal Relations.